Evolution of NATO and Development of a New European Security System. The Future of Europe and US Relations. - Pilosio, Giuseppe (1998)
Since the fall of the Berlin Wall the security architecture in Europe has substantially changed. For many, the end of the Cold War reflected a possible end of NATO's existence. The prediction of NATO's inevitable demise has so far been wrong. NATO is still in good shape, but the NATO of yesterday does not exist anymore. The Alliance has been downsized, reorganized, redeployed and regenerated under a different concept. To summarize, the organization has undertaken a double process of adaptation, internally and externally. Internally, NATO military forces have reduced their size and readiness, improved their mobility, flexibility and adaptability to different contingencies and relied on a greater use of multinational formations. In addition, an agreement on a new command structure that foretells a reduction from 65 headquarters at present to 20 has been reached. Externally, NATO has opened itself to the East by creating at first the North Atlantic Cooperation Council and in 1994 the Partnership for Peace program. In addition, the Alliance has remained open to membership of other European countries. To date, twelve nations have asked to join NATO and three have already signed the Protocols of Accession. In the meantime, the European Union Member States "reactivated" the Western European Union (WEU) in an effort to establish a European Security and Defense Identity. In 1996, the WEU was given permission to conduct its own military missions using NATO assets, through the concept known as Combined Joint Task Force. These decisions have created the conditions for a valid European defense system. Now the question is to identify a more suitable equilibrium between the two "pillars" of the Atlantic Alliance, American and European. Equilibrium that is essential for the future of European and U.S. relations.